Mechanical Behavior and Failure Analysis of Prosthetic Retaining Screws after Long-term Use In Vivo. Part 3: Preload and Tensile Fracture Load Testing - Youssef S. Al Jabbari, BDS, MS, PhD,1 Raymond Fournelle, PhD,2 Gerald Ziebert, DDS, MS,3 (Journal of Prosthodontics, 2008)
The aim of this study was to determine the preload and tensile fracture load values of prosthetic retaining screws after long-term use in vivo compared to unused screws (controls).